Integrated double signal amplification systems with ELISA assay for sensitive detection of tylosin in food - Shan Shan; Xi Lv; Xiaoyue Xiao; Yanmei Huang; Xiaoyu Tong; Weihua Lai; Chengwei Liu; Shuanglong Wang; Daofeng Liu (Food and Agricultural Immunology)
Tylosin (TYL) is a kind of antibiotics which promotes the development of animal husbandry, but it poses potential threats to food safety and human health. Therefore, it is necessary to establish a highly sensitive method for the detection of TYL. Here, an enzyme-linked immunosorbent assay (ELISA) combined with biotin–streptavidin (Bio-SA) system and hybridization chain reaction (HCR) technique (Bio-SA-HCR-ELISA) was developed. In the absence of the TYL, a strong fluorescence was generated through double signal amplification as signal output, while in the presence of TYL, the fluorescence intensity decreased. The results showed that the limit of detection for TYL was 0.39 ng/mL, and this method had a good specificity for 9 common antiboics. Compared to the traditional indirect competitive ELISA, the sensitivity of this method was 6.8 times higher. Additionally, the established double signal amplification Bio-SA-HCR-ELISA was used for detecting TYL in milk and honey, the LOD of this method were 4.9 and 2.5 ng/mL, respectively.